Ketergantungan penggunaan AI pada pendidikan tinggi: Ancaman terhadap keterampilan membaca teks akademik - Pujiastuti, Indah; Damaianti, Vismaia S.; Mulyati, Yeti; Sastromihardjo, Andoyo; Lestari, Dian (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
This study investigates the relationship between students’ dependence on the use of AI Chatbots for academic purposes and students’ ability to read academic text. The study was a correlational design on 39 students of the Indonesian Language Education Program a university in Indonesia. Dependence on the use of AI was assessed through a questionnaire; academic reading ability was measured through an essay test. The data were analyzed using SPSS with Pearson’s, with effect size (r) and significance (p) reported. The results showed that the participants had a moderate dependence on AI Chatbots (M=2,78; SD=0.64) and reading scores in the basic category (M=47,74; SD=16,67). A weak but significant negative correlation was found (r = -0,370; p = 0,020). These results prove that a higher dependence on AI use can be associated with reduced cognitive ability in reading academic texts. Although limited by a small sample and the scope of one university, this study offers preliminary evidence about the risks of using AI in language education, especially reading academic texts, which runs counter to the assumption that AI is universally beneficial. This study recommends large-scale research in various contexts.